Pengaruh Kedalaman Alur Ban dan Tekanan Ban Terhadap Gaya Pengereman - Kurniawan, Tegar; Muchtar, Agus; Burhanudin, Aan (CV. IRA PUBLISHING, 2025)
This study analyzes the effect of tire tread depth and tire pressure on braking force in a Mitsubishi L300 vehicle. An experimental method was applied with variations in tread depth (>1 mm and <1 mm) and tire pressure (30 psi, 50 psi, and 60 psi). Results indicate that both variables significantly affect braking efficiency. The 50 psi–50 psi combination at >1 mm tread depth yielded the highest efficiency (86%), whereas the 30 psi–30 psi combination at <1 mm tread depth recorded the lowest (48%). A tread depth of <1 mm reduced braking efficiency by 15–20% on average. Tire pressures below or above the standard decreased braking performance by 10–15%. Maintaining balanced tire pressure at 50 psi and a minimum tread depth of 1 mm is recommended for driving safety.